Incidencia del desempeño fiscal en el desarrollo social de los municipios del país 2008-2013 (2016)
From the emission of the Law 617 from 2000, the country’s municipalities have adjusted their operating costs and improving their own arrangements, allowing them to improve their finances and consolidate its fiscal performance. Under these circumstances, social development should be benefited, because there are more resources to meet their huge social needs. Hence, the importance of a socio-tax study where tax and social outcomes of different municipal entities are integrated.